Does parvovirus B19 have a role in rheumatoid arthritis?. Issue 2 (February 1994) - Nikkari, S; Luukkainen, R; Möttönen, T; Meurman, O; Hannonen, P; Skurnik, M; Toivanen, P
Abstract : OBJECTIVES--To determine whether parvovirus B19 (B19) infection is associated with rheumatoid arthritis (RA). METHODS--The polymerase chain reaction was applied to serum, cells isolated from synovial fluid, and synovial fluid. Enzyme immunoassay technique was used to detect antibodies against B19. RESULTS--Of 142 patients with early RA (onset of disease under one year) and 67 control patients, serological evidence of recent parvoviral infection was found in 4/135 and 2/62, respectively. However, no evidence for the presence of parvoviral DNA was observed in 18 synovial fluids, 21 samples of synovial fluid granulocytes or 40 sera, all obtained from 65 patients diagnosed with early RA. CONCLUSION--Although there is published evidence of chronic rheumatoid-like arthropathy following acute parvovirus infection, our findings do not support the involvement of B19 in the aetiopathogenesis of RA.